Heat shock protein B1-mediated ferroptosis regulates mitochondrial dysfunction in adipose tissue of ketotic dairy cows - Fan, Yunhui; Ma, Li; Xu, Xinyi; Fang, Xinxin; Mauck, John; Loor, Juan J.; Sun, Xudong; Jia, Hongdou; Xu, Chuang; Xu, Qiushi (Journal of dairy science, 2025)
The list of standard abbreviations for JDS is available at adsa.org/jds-abbreviations-24. Nonstandard abbreviations are available in the Notes. In the peripartal period, dairy cow adipose tissue undergo significant metabolic challenges, including oxidative stress and endoplasmic reticulum stress, which could be alleviated by inhibition of ferroptosis. Oxidative stress is often accompanied by mitochondrial damage. However, whether mitochondrial dysfunction occurs in the adipose tissue of ketotic cows are still unclear. Heat shock protein B1 (HSPB1), a key regulator of cellular redox homeostasis, is critical in managing oxidative stress and iron metabolism. Thus, this study aimed to investigate the role of HSPB1-mediated ferroptosis on mitochondrial dysfunction of adipocytes of ketotic dairy cows. We collected adipose tissue samples of clinical ketosis cows (n = 15) with a serum BHB concentration of 3.14 mM (interquartile range = 0.11) and healthy cows (n = 15) with a serum BHB concentration of 0.55 mM (interquartile range = 0.12). Compared with the healthy control group, the protein abundance of HSPB1, transferrin (TF), transferrin receptor 1 (TFR1), 6-transmembrane epithelial antigen of the prostate family member 3 (STEAP3), divalent metal transporter 1 (DMT1), and acyl-CoA synthetase 4 (ACSL4), as well as levels of reactive oxygen species, Fe2+, and total iron were greater in adipose tissue of ketotic cows. Ketotic cows exhibited lower ferroportin (FPN), solute carrier family 7 member 11 (SLC7A11), glutathione peroxidase 4 (GPX4), mitochondrial oxidative phosphorylation complexes I–V (CO I–V), peroxisome proliferator-activated receptor gamma coactivator 1-α (PGC-1α), mitofusin-2 (MFN2), nuclear respiratory factor 1 (NRF-1), and mitochondrial transcription factor A (Tfam) protein expression levels, along with lower ATP content compared with control cows. Epinephrine (EPI) treatment upregulated protein abundance of HSPB1 and induced ferroptosis and mitochondrial dysfunction in adipocytes. Inhibition of ferroptosis by pretreatment with ferrostatin-1 (Fer-1) attenuated the EPI-induced decrease in ATP content. Knockdown of HSPB1 by small interfering RNA (si-RNA) exacerbated the EPI-induced upregulation of TF, TFR1, STEAP3, and DMT1 expression and the downregulation of FPN protein expression levels. Furthermore, in the presence of EPI and HSPB1 si-RNA, Fer-1 abolished the regulatory role of HSPB1 on mitochondrial dysfunction, confirming that HSPB1 regulates bovine adipocyte mitochondrial dysfunction in a ferroptosis-dependent manner. Collectively, these data suggest that HSPB1-mediated ferroptosis is an important regulatory mechanism for mitochondrial dysfunction in adipocytes of peripartal dairy cows under negative energy balance.